Social Media as a Tool for Transforming Childhood Learning Mechanisms in Edupreneurship - Watini, Sri; Magdalena, Lena; Wirjawan, Tri Wahyu; Gunawan, ⁠Ahmad; Julianingsih, Dwi; Ivanov, Nikita (Pandawan, 2025)
This paper delves into the intricate relationship between social media and childhood learning mechanisms for children. Despite the growing body of research on learners acceptance of e-learning systems via childhood program platforms, a considerable gap remains in understanding the determinants that shape the acceptance of e-learning facilitated through social media applications. Addressing this gap, our study undertakes an exploration of the impact of social media practices, specifically knowledge sharing, social media features, motivation, and uses, on children embrace of e-learning systems. To accomplish this, we extend the well-established Technology Acceptance Model (TAM) to incorporate these determinants. A comprehensive survey was conducted involving 355 children. These students participated through questionnaire surveys, providing essential empirical data. Employing the robust SmartPLS technique, meticulously analyzed the extended model. The results of empirical data analysis demonstrate that social media practices exert a significant and positive influence on Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) related to Childhood Learning Mechanisms. Crucially, our findings underscore the pivotal role of both PU and PEOU in influencing the acceptance of e-learning systems. In essence, this paper not only sheds light on the transformative potential of social media practices in shaping the acceptance of e-learning systems but also contributes to the existing discourse by deepening our understanding of the interplay between social media, TAM determinants, and e-learning acceptance in childhood programs.